Agricultural Land Use Change and Livelihood Vulnerability in the Expansion Area: Pangandaran Regency - Muthiah Syakirotin; Lies Sulistyowati; Trisna Insan Noor; Ahmad Choibar Tridakusumah (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The expansion areas have experienced a decline in agricultural land use and a decrease in the number of farming households, which has an impact on livelihood transformation. The purpose of this study is to analyze changes in agricultural land use and the vulnerability of farmers' livelihoods in the expansion areas, namely Mangunjaya Sub-district and Padaherang Sub-district of Pangandaran Regency. This research uses a quantitative descriptive method with a spatial analysis approach and an interview technique of 378 farmers. The highest land area change in Mangunjaya sub-district was gardens by 44% while in Padaherang Sub-district it was water bodies by 48%. The highest vulnerability is pressure with a value of 4.65 where there are indicators of agricultural land conversion. Changes in agricultural land use show an impact on the vulnerability of farmers' livelihoods as evidenced by disasters on agricultural land, a decrease in agricultural production and diversification of livelihoods other than the agricultural sector. Comprehensive efforts involving the government, community, and private sector are needed.